Foreign Debt in the Perspective of Tafsir Fii Zilaal Al-Qur'an by Sayyid Qutb - Muhamad Komarudin (El-Qish: Journal of Islamic Economics, 2021)
This study aimed to analyze the contemporary interpretation of Sayyid Qutb against usury contained in foreign debt in his book Fii Zhilaal al-Qur'an Surah Al-Baqarah: 275. The method used in this research is the descriptive analysis method combined with the method of hermeneutics and supported by a literature review to find Sayyid Qutb’s thoughts on foreign debt. This study is an attempt to gain a proper understanding of usury-based on a contemporary interpretation of Sayyid Qutb in the book Fii Zhilaal Al-Qur'an especially that including in foreign debt. This study described the analysis of usury in foreign debt base on the interpretation of Sayyid. Findings. The results of this study are understandings of the thoughts of Sayyid Qutb in his book related to the impact of foreign debt which may lead to the theory that foreign debt will have an impact on regulatory intervention, colonization, and even warfare.